A comparative study on wound outcome after non approximation against approximation of subcutaneous layer during emergency caesarean section in patients with abdominal subcutaneous layer > 2 cm - Saumya; Amitava Das; Sandip Sarkar; Chiranjit Ghosh; Abhinav Shrivastava (Barpeta Obstetrics and Gynaecological Society, 2020)
Objective: The objective of this study is to compare the outcome of caesarean section post-op wound in patients after either approximation or after non-approximation of the subcutaneous fat layer. Methodology: 390 women who underwent emergency caesarean section having abdominal fat thickness of more than 2 cm were randomly allocated in two groups of 195 each. The subcutaneous fat layer was approximated in the patients of group A. The condition of wound in each patient was examined on 5th postoperative day and the complications, if any were categorised into wound disruption, seroma, hematoma or infection. Then further postoperative analgesic, antibiotic doses and hospital stay duration were compared among two group patients. Result: Among 195 patients of Group A, only 20 (10.26%) had wound complications whereas in Group B, 55 patients had wound complications (28.21 %). In group A patients, only 2.5 % needed secondary suturing whereas in group B patients, 18.9 % needed secondary suturing. Conclusion: Approximation of the subcutaneous tissues separately significantly reduces wound complications, requirement of secondary suturing along with a significant reduction in the duration of hospital stay.